Morphometric Assessment of Tibial Tuberosity and its Clinical Relevance in Indian Population - Swati G.,; Rajan KS.,; Jagdev K.,; Gaurav A.,; Vandana M.,; Rajesh KS., (Department of Surgery, UKM Medical Centre, 2015)
Morphometric parameters of tibial tuberosity can be used to guide treatment and monitor outcome of total knee replacement surgeries. Tibial tuberosity being a tractional apophysis can be a site for recurrent avulsion fractures. Morphometric measurements of tibial tuberosity of 100 adult human tibiae were meticulously recorded with the help of Vernier calipers. Student’s t-test was used for statistical analysis with significant level of < 0.05 and 95% confidence interval. The mean distance of tibial tuberosity from the anterior border of intercondylar area was found to be more in males on both sides and statistically significant only on right side (p-value=0.020 on right side). The length of upper smooth and lower rough part of tibial tuberosity were statistically significant on right side (p-value=0.001 and 0.019, respectively). Furthermore, comparison between the two sides of upper smooth part of tibial tuberosity showed the difference being statistically significant only in females (p-value= 0.027 in females). The mean values of breadth of upper smooth and lower rough part of tibial tuberosity were found to be statistically significant on both the sides (p-value on right side = 0.009 and on left side=0.002; p-value on right side=0.008 and on left side=0.012). The present study is an endeavor to provide a base line data with reference to unicompartmental and total knee arthroplasty in Indian population. The results of this research work assume special importance in view of the technical advancements in reconstructive surgical procedures in orthopedic practice.